TIDAK ADA PERBEDAAN PENGARUH DEEP NECK FLEXORS STRENGTHENING EXERCISE DENGAN SCAPULAR STABILIZATION EXERCISE UNTUK PERBAIKAN FORWARD HEAD POSTURE - Adinda Dwi Nurul Azmi; nia kurniawati; Erna Sariana (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: One of the posture disorders experienced by adolescents is forward head posture. Methods:This research uses quasi experimental group with two group pre-test post-test design. Research sample population is 15–17 years old students with 16 persons on each groups. The 1stgroup given deep neck flexor strengthening exercise and the 2ndgroup given scapular stabilization exercise.Intervention is performed 9 times with 3 times repetition in a week. The measurement of this research is craniovertebral angle. Normality test used Shapiro-wilk test, homogeneity test used wilcoxon test, and the test of difference of intervention impact given is performed by mann whitney test. Result: The value of intervention impact test of 1stgroup is p=0,000, the 2ndgroup test results the value of p=0,000. The result of both diference impact, results value of p=0,597. Conclusion: There is no difference between twointervention